STUDI TENTANG EFEKTIVITAS ALAT PENGENDALI KECEPATAN PADA KAWASAN ZOSS DI KOTA PONTIANAK - Farizaldin, Muhammad; AS, Syafaruddin; Suyono, Rudi S. (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
rumble strip is a warning device is physically allocated to the driver of the vehicle in order to further enhance alertness. From the results of the analysis, it is known that the effectiveness of the band wrapping on the ZoSS area at the location of the primary collector road function (the location of Tanjung Raya 2 and Hasanuddin roads) and the secondary collector (Jendral Urip and Merdeka roads) affect the 0.00% effectiveness percentage especially for Tanjung Raya 2 roads, while the effective speed control for the secondary collector Road function is in the range of 40.00%. in the schools studied there were schools that were not equipped with school signs, as well as signs that were blocked by trees. speed data retrieval using a speed gun. The solution to improve the effectiveness of the band wrapping is the design and arrangement of rumble strips that need to be updated and added facilities that support the performance of rumble strips in the form of adding a minimum height of 2 cm with a distance of 100 cm, sowing additional facilities in the form of warning lights, and adding special markers red and markers are prohibited from parking